SPEED READING TO IMPROVE STUDENT’S READING SKILL - Mahriza, Rita (JL3T (Journal of Linguistics, Literature and Language Teaching), 2016)
This study is to find out whether speed reading improves student’s reading skill of the eleventh grade students at SMA Negeri 2 Langsa. The population of this research is the entire eleventh grade students at SMAN 2 Langsa. This study used quazy experiment. Test in the form of multiple choices through speed reading was used as instrument of this study. It is found that the result of pre-test and post-test in both experimental and control class is different. In experiment class, the average score of multiple choices test is higher than thatof control class. Based on t-test analysis, it was found that the t score(2,02)> ttable(2,71). It can be concluded that tscore is higher than ttable, thus hypothesis is accepted. Meanwhile, in control class, the students’ average score of speed test was 135 WPM and improves at least 1832 WPM in experiment class. The students’ reading skill of SMAN 2 Langsa in speed test is good. 1 students in experiment class secured A and no student obtained the same grade in control class. 9 students in experiment class got B while only 5 students from control class obtained the same score. It shows that experiment class performs better than that of control class. Thus, teaching reading skill by using speed reading at SMAN 2 Langsa is successfull and proves that speed reading improves students’ reading skill.